The reasons of failed democracy in Belarus - Ramūnas Davidonis (Politologija)
Samuel P. Huntington has come to notice that the primary source for the most serious threats to the evolving democracies of the third wave unfold from within, the political leaders and groups, which, once the elections are won and the power—seized, manipulate upon the democratic mechanisms. Hence, when the elected chief executive concentrates the power in his own hands, subordinates or even suspends the legislature, and rules largely by decree, the democratic mechanisms turn first suppressed and later—abolished.